As prisões da reforma I: a reforma penitenciária em questão - Arangurí, Martín (2009)
This study aims to deconstruct prison in historical and political terms. For that purpose, it avails itself of concepts that mark its thresholds, limits and tipping points. The dissertation s major underlying question is: How does an institution so criticized, reviled and slandered such as prison is able to endure for so long, thrive more and more, and show so much resilience? Prison s ability to pick itself up and continually expand even after being denounced and accused of major and minor failures is something that brings about a measure of reverence for the deed and a bit of uncertainty about the phenomenon. That is enough to provoke a lot of interest and a significant number of suspicions. The utmost care was taken to think outside the box herein. With regard to prison, that means challenging reform. Thus, this paper cannot have any commitment to the State s pressing needs. But -- how so? Well, from what has been scribbled on prisons so far, few are those records that can brag about not being reform manuals or a political institution s moralizing guide. Such writings even have a course of action very similar to the works that drive away readers because of the tedium they emanate: 1) they comply with a timeline; 2) they go back to ancient times when everything was, in the nitwits opinion, more barbaric, raw and stupid; and 3) they reach our days, a moment of relief for the evil which was left behind mixed with a disappointment for what could have been performed a lot better. So, they go on to analyze the minutia of every single failure in the several manifestations of the phenomenon in question; they begin the swarm of advices to governments and authorities, who someday may acquire enough judgment to direct individuals without excesses or wastes, in the full force of the law. Evolution, investigation, recommendation. Beginning, middle and ending of the works on prison reform. That is when this paper, spurred by the verification of these discourses common matrix, decides to frighten away its own yawning by jumping up and down, demarcating topics and subjects in the examination s progression-regression-perdition, while it averts the boring, flat time so that it is able to go ahead, come back and lose itself when necessary. Throughout its trajectory, it sought to dig an abyss between that science which provides a doctoral assistance to govern, control and master better and that knowledge which only announces its own design by sliding among doubts and queries under an avalanche of problems upon problems